The Role of CEO as Succession Planning in Family-Owned Businesses : The Case of Small and Midsized Czech Manufacturing Firms - Iasynska, Anna (2025)
This bachelor thesis investigates the influence of the CEO role as a critical factor in succession planning within small and midsized family-owned manufacturing firms in the Czech Republic. Succession in family businesses is a complex and multifaceted process that significantly affects business continuity and long-term success. The study aims to assess how CEOs contribute to effective generational transitions by exploring their leadership strategies, the family systems in place, organizational development practices, and methods for employee retention and team building. Using qualitative and quantitative data collected from Czech family firms, the research identifies transformational and participatory leadership styles as key to successful succession. It also highlights the importance of formal governance structures and clear role delineation between family and business to mitigate conflicts and foster organizational resilience. The findings emphasize that proactive CEO involvement, combined with inclusive employee engagement, enhances the likelihood of smooth and sustainable generational transitions. This thesis contributes valuable insights for family business owners, advisors, and policymakers seeking to improve succession planning practices in the Czech SME manufacturing sector.